Robust consensus control of uncertain multi‐agent systems with input delay: a model reduction method - Zuo, Zongyu; Wang, Chunyan; Ding, Zhengtao (International journal of robust and nonlinear control, 2017)
Summary This paper addresses the robust consensus control design for input‐delayed multi‐agent systems subject to parametric uncertainties. To deal with the input delay, the Artstein model reduction method is employed by a state transformation. The input‐dependent integral term that remains in the transformed system, owing to the model uncertainties, is judiciously analysed. By carefully exploring certain features of the Laplacian matrix, sufficient conditions for the global consensus under directed communication topology are identified using Lyapunov–Krasovskii functionals in the time domain. The proposed control only relies on relative state information of the subsystems via network connections. The effectiveness and robustness of the proposed control design are demonstrated through a numerical simulation example. Copyright © 2016 John Wiley & Sons, Ltd.